1996
DOI: 10.1364/josab.13.000560
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional coupling owing to optical nonlinearities II Results

Abstract: We compare three computational techniques developed in the preceding paper [J. Opt. Soc. Am. 13, 553 (1996)] that account for the effects of nonlinear coupling on light propagating through nonlinear, dispersive media. We demonstrate that all three techniques give reasonable accuracy under conditions typical of a self-modelocked laser. We further show that these techniques are greatly superior to techniques that neglect nonlinear coupling in that they give results that are more accurate and, in some cases, qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…12is often a good approximation. We demonstrate this in the accompanying paper 26 by considering a specific example of a pulse propagating in a nonlinear medium and comparing the numerical results obtained with and without the assumption of Eq. 12.…”
Section: Fourier-transform Techniquesmentioning
confidence: 85%
See 1 more Smart Citation
“…12is often a good approximation. We demonstrate this in the accompanying paper 26 by considering a specific example of a pulse propagating in a nonlinear medium and comparing the numerical results obtained with and without the assumption of Eq. 12.…”
Section: Fourier-transform Techniquesmentioning
confidence: 85%
“…We have presented three computational techniques, two of which were derived for the first time to our knowledge, for including the effects of nonlinear coupling on the propagation of light through nonlinear, dispersive media. In the paper that follows 26 we compare the accuracy of these three techniques. We also show how to propagate through optical elements and inside cavities, and we demonstrate the importance of nonlinear coupling by considering a specific self-mode-locked laser as an example.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was shown that the effect should be included in the previously mentioned theory. Descriptions incorporating both the spatial beam alteration and nonlinear coupling produce more accurate results [9].…”
Section: Mode Lockingmentioning
confidence: 99%